Implementasi Product Awareness Pada Proses Produksi Iklan “raja Smartphone Lipat Baru, Oppo Find N3” Di Detikcom - Azzam, Muhammad; Melano, Fiqie Lavani (eProceedings of Management, 2024)
The development of the digital era has made the internet a means of media to obtain information. Advertising is oneof the media means of providing information with the aim of attracting the attention of potential customers or thegeneral public that has persuasive characteristics. Companies from various sectors have advertised their productsthrough the internet, one of which is OPPO such as the product advertised is OPPO Find N3. Various mediacompanies have been entrusted in broadcasting this latest product, one of which is detikcom. The production processof making this advertisement will be discussed to further examine how to apply product awareness on OPPO Find N3content at detikcom. With the method of in-depth observation in the field, this work is expected to provide insight intothe application of production awareness in the ad production process starting from pre-production, production, topost-production. Keywords-advertisement, product awareness, production procces.